Oppression, liberation, wellbeing, and ecology: organizing metaphors for understanding health workforce migration and other social determinants of health - Akhenaten Benjamin Siankam Tankwanchi (BMC, 2018)
Abstract Background The Commission on Social Determinants of Health (CSDH) identifies the maldistribution of power, money, and resources as main drivers of health inequities. The CSDH further observes that tackling these drivers effectively requires interventions to focus at local, national, and global levels. Consistent with the CSDH's observation, this paper describes the eco-psychopolitical validity (EPV) paradigm, a multilevel and transdisciplinary model for research and action, thus far insufficiently tapped, but with the potential to systematize the exploration of the social determinants of health. Results Using the physician migration from Sub-Saharan Africa (SSA) to the United States as illustration, this paper articulates how the EPV model can be applied to the systematic analysis of a complex social problem with health inequity implications. To help explore potential determinants of physician migration, a comprehensive coding matrix is developed; with the organizing metaphors of the EPV model-namely oppression, liberation, and wellbeing-serving as analytical categories. Through the lens of the EPV model, migrating physicians are revealed as both ecological subjects enmeshed in a vast web of transnational processes linking source and destination countries, and potential change agents pursuing liberation and wellbeing. While migration may expand the opportunities of émigré physicians, it is argued that, the pursuit of wellbeing by way of migration cannot fully materialize abroad without some efforts to return home, physically or socially. Conclusion Clarifying the relationship between various social determinants of health and health inequities at different levels of analysis is a more complex but essential endeavor to knowledge generation than using a one-dimensional frame. With its roots in interdisciplinary thinking and its emphasis on both individual and contextual factors, the EPV paradigm holds promise as a model for examining the social determinants of health.